THE INFLUENCE OF CLIMATE FACTORS ON DIARRHEA CASES IN CHILDREN UNDER FIVE YEARS BEFORE AND AFTER THE COVID-19 PANDEMIC IN BANJARMASIN - Budiyanto Budiyanto (Berkala Kedokteran, 2022)
Abstract: Background: Diarrhea still become one of the leading causes of morbidity and mortality in children, especially under 5 years. Anthropogenic climate change, mainly due to global warming process, is expected to change the epidemiological pattern of infectious diseases, including diarrhea. COVID-19 pandemic that has occurred globally since March 2020 may also have an impact. Banjarmasin as a city in a wetland area with tropical savanna climate that also affected by COVID-19 pandemic is also at risk. We conducted a research to study the influence of climate factors on diarrhea cases in children under 5 years before and after the COVID-19 pandemic in Banjarmasin.Methods: Data of monthly diarrhea cases in children under 5 years at public health centers from Banjarmasin City Health Office and monthly climate data (amount of rainfall, number of rain days, temperature, humidity, sunshine duration, wind speed) from BMKG and BPS between January 2010 to April 2021 were collected. Statistical analysis was carried out to determine the correlation between climate factors and diarrhea cases before and after COVID-19 pandemic.Results: There was a decrease in the average monthly visits of children under five years with diarrhea before (497 ±47.4) and after (132 ±45.8) COVID-19 pandemic. Among climate factors, amount of rainfall (r=-0.753; p=0.005), number of rain days (r=-0.774; p=0.003), and humidity (r=-0.590; p=0.044) were negatively correlated, while sunshine duration (r=0.674; p=0.016) was positively correlated with diarrhea cases in the period before COVID-19 pandemic. No correlation was found between any climate factor and diarrhea cases in the subsequent period.Conclusion: Diarrhea cases in children under 5 years in Banjarmasin tend to increase in dry season, however during COVID-19 pandemic there were some changes in society, such as working from home, reluctance to go to health facilities which might affect the usual trend. Keywords: Anthropogenic climate change; Climate factors; COVID-19 pandemic;  Diarrhea under 5 years; Wetland